Gross primary productivity of phytoplankton and planktonic respiration in inland floodplain wetlands of southeast Australia: habitat‐dependent patterns and regulating processes. Issue 5 (26th June 2013) - Kobayashi, Tsuyoshi; Ralph, Timothy J.; Ryder, Darren S.; Hunter, Simon J.
Abstract: Gross primary productivity (GPP) of phytoplankton and planktonic respiration (PR) (i.e., planktonic metabolism) are critical pathways for carbon transformation in many aquatic ecosystems. In inland floodplain wetlands with variable inundation regimes, quantitative measurements of GPP and PR are rare and their relationships with wetland environmental conditions are largely unknown. We measured PR and the GPP of phytoplankton using light and dark biological oxygen demand bottles in open waters of channel and non‐channel floodplain habitats of inland floodplain wetlands of southeast Australia that had been inundated by environmental water. Overall, GPP varied from 3.7 to 405.5 mg C m −3 h −1 (mean ± standard error: 89.4 ± 9.2 mg C m −3 h −1, n = 81), PR from 1.5 to 251.6 mg C m −3 h −1 (43.2 ± 5.6 mg C m −3 h −1, n = 81), and GPP/PR from 0.2 to 15.6 (3.0 ± 0.3, n = 81). In terms of wetland environmental conditions, total nitrogen (TN) ranged from 682.0 to 14, 700.0 mg m −3 (mean ± standard error: 2, 643.0 ± 241.6 mg m −3, n = 81), total phosphorus (TP) from 48.0 to 1, 405.0 mg m −3 (316.8 ± 31.4 mg m −3, n = 81), and dissolved organic carbon (DOC) from 1.9 to 46.3 g m −3 (22.0 ± 1.6 g m −3, n = 81). Using ordinary least‐squares multiple regression analyses, the rates of GPP and PR, and their ratio (GPP/PR) were modeled as a function of TN, TP, and DOC that had been measured concomitantly. The "best" models predicted GPP and GPP/PR ratio in channel habitats as a function of DOC; and GPP, PR, and GPP/PR in non‐channel floodplain habitats as a function of TN and/or TP. The models explained between 46 and 74 % of the variance in channel habitats and between 17 and 87 % of the variance in non‐channel floodplain habitats. Net autotrophy (mean GPP/PR 3.0) of planktonic metabolism in our work supports the prevailing view that wetlands are a net sink for carbon dioxide. We propose a nutrient‐DOC framework, combined with hydrological and geomorphological delineations, to better predict and understand the planktonic metabolism in inland floodplain wetlands.